Pembuatan Aplikasi Buku Tamu Berbasis Website di Kelurahan Afa-Afa - Alfanugrah A. Hi Usman; Muhammad Fhadli; Abdul Mubarak; Mustamin Hamid (BADAN PENERBIT STIEPARI PRESS, 2022)
The guest book is an important thing that is used to record visitor data at the Afa-afa sub-district office which aims to find out who is visiting and the purpose and purpose of the visit. The results of observations, it was found that until now the process of recording guest books in the afa-afa village is still conventional and is done manually using paper so that archiving and documents that have been recorded are often lost and irregular. Based on the existing problems, through this community service, a guest book website will be created which can make it easier to record every visit to the Afa-Afa village office and make visit data safer. The output target in community service is the existence of a service journal and a website that can be used by the afa-afa village.